Penerapan Data Mining Penilaian Afdeling Terbaik Menggunakan Algoritma CART pada PTPN II Langkat - Rizki Rianda; Suendri, Suendri (Program Studi Teknik Informatika Universitas Pamulang, 2024)
In an afdeling, the oversight cycle should be done by an afdeling head. The PTPN II Langka assembly unit assessment process is not carried out in a professional manner; rather, it is based on the assembly's output. This will result in assessment results that are not in line with the anticipated qualifications and are deemed to be less effective. Aside from that, it is conceivable that there will be comparable creation brings about other afdelings so it is extremely challenging to decide the best afdeling that meets the normal capabilities. This happens in light of the fact that there is no deliberate standard strategy for evaluating the appropriateness of the best connection unit. The CART algorithm was used to classify the best afdeling based on existing variables in order to provide results that could simplify and lighten the Head of PTPN II Langkat's work and make it easier to choose the best afdeling. System development makes use of the Rapid Application Development (RAD) methodology